Exploring the mediatization of organizational communication by religious communities in digital media - Knudsen, Gry Høngsmark; Nielsen, Marie Vejrup (MedieKultur: Journal of media and communication research, 2019)
This article presents an exploratory study of some of the ways in which religious communities communicate as organizations in digital spaces. Based on previous research, the article examines the extent to which processes of mediatization are visible in the digital spaces utilized by religious communities in Denmark today. The study is based on data from websites and Facebook groups from ten Christian churches: five ELCD (Evangelical Lutheran Church in Denmark) parishes and five free churches. Data was collected using methods particularly designed for collecting digital data, with due consideration of the ethical implications of researching religious identity online. The data collection represents a follow-up study to the research project Religion in Aarhus 2013. Based on our findings, we suggest that mediatization processes progress more slowly in institutional religious communication because of the way in which they are organized. Furthermore, we demonstrate that there are some patterns in the way Christian communities express themselves online, and that these patterns to some extent depend on whether an ELCD parish or a free church is involved.